Sustainable Financial Management in MSMEs: A Qualitative Study of Green Business Adaptation in Indonesia - Syahrul Syarifudin; Dendi Purnama (Jurnal Bisnis dan Kewirausahaan, 2026)
This study aims to explore how Micro, Small, and Medium Enterprises (MSMEs) in Indonesia implement sustainable financial management within the context of green business adaptation. The study employed a qualitative exploratory approach involving 15 MSME owners operating in the food and beverage, fashion, handicraft, and eco-friendly product sectors. Data were collected through semi-structured interviews and direct observation, then analyzed using thematic analysis. The findings reveal that sustainable financial management among MSMEs is primarily implemented through operational efficiency, waste reduction, environmentally responsible resource allocation, and gradual adaptation toward sustainable business practices. Sustainability adaptation is strongly influenced by owner-manager values, customer expectations, market pressures, and organizational learning processes. The study also found that sustainable financial management contributes positively to organizational resilience, customer trust, and long-term business confidence. However, MSMEs continue to face challenges related to limited financial resources, restricted access to green financing, inadequate sustainability knowledge, and insufficient institutional support. The study contributes theoretically by strengthening Sustainable Financial Management Theory within MSME contexts and practically by providing insights for policymakers and business development institutions in supporting sustainability transformation among small businesses in Indonesia.